Analisis Faktor Determinan Pelaksanaan Inisiasi Menyusu Dini Oleh Bidan Di Rumah Sakit Umum Anutapura Palu - Novita, Ni Nyoman; Arsyad, Gusman (Jurnal Bidan Cerdas, 2018)
Implementation of IMD in hospitals has decreased from the previous year and has not reached the target set by the government. Some IMD implementation processes have not been carried out according to applicable standards. So that babies do not get an IMD in accordance with existing SOPs. The purpose of this study was to determine the determinant factors associated with the implementation of the IMD by midwives in the Midwifery and Maternity Room Emergency Room (IGD) at the Anutapura General Hospital in Palu. This research method is analytical with cross sectional approach. The population of this study was that all midwives in the obstetrics emergency room and maternity room at Anutapura Palu Hospital were 37 respondents. The sample in this study is total sampling. The analysis used was univariate, and bivariate analysis using the chi square test with a confidence level of 95% (α = 0.05). The results of statistical tests on variable knowledge of midwives with the implementation of IMD p value: 0.018 (p value <0.05). APN training with the implementation of IMD p value: 0.697 (p value> 0.05). length of work with the implementation of IMD p value: 0.029 (p value <0.05). and peer support with the implementation of IMD p value: 0.007 (p value <0.05). Conclusions there is a relationship between knowledge, length of work, peer support with the implementation of the IMD, and training factors that have nothing to do with IMD implementation. The strongest factor in the relationship is peer support. It is recommended that the Anutarapura Palu Hospital be able to motivate midwives so that they can further enhance their role in the implementation and provide support to their colleagues so that the implementation of the IMD can be carried out in accordance with applicable standards.Keywords: Knowledge, APN Training, Duration of work, Implementation of IMD